2022
DOI: 10.1007/s11095-022-03445-1
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Microparticles Show Similar Efficacy With Lipid Nanoparticles in Delivering mRNA and Preventing Cancer

Abstract: Purpose Messenger RNA (mRNA) has shown great promise for vaccine against both infectious diseases and cancer. However, mRNA is unstable and requires a delivery vehicle for efficient cellular uptake and degradation protection. So far, lipid nanoparticles (LNPs) represent the most advanced delivery platform for mRNA delivery. However, no published studies have compared lipid microparticles (LMPs) with lipid nanoparticles (LNPs) in delivering mRNA systematically, therefore, we compared the impact of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…There are some questions that what is the difference between microparticles and nanoparticles in the treatment of cancer? Interestingly, a recent experiment has shown that lipid microparticles have a similar potential to lipid nanostructures to deliver mRNA and impair the progression of cancer [ 47 ]. Moreover, an improvement in the cancer therapy has been obtained through application of stimuli-responsive nanocarriers such as glutathione-responsive mesoporous nanostructures that active both immune system and mediate chemotherapy in the tumor suppression [ 48 ].…”
Section: Nanoparticles In Tumor Therapymentioning
confidence: 99%
“…There are some questions that what is the difference between microparticles and nanoparticles in the treatment of cancer? Interestingly, a recent experiment has shown that lipid microparticles have a similar potential to lipid nanostructures to deliver mRNA and impair the progression of cancer [ 47 ]. Moreover, an improvement in the cancer therapy has been obtained through application of stimuli-responsive nanocarriers such as glutathione-responsive mesoporous nanostructures that active both immune system and mediate chemotherapy in the tumor suppression [ 48 ].…”
Section: Nanoparticles In Tumor Therapymentioning
confidence: 99%
“…[ 133 ] Due to the instability of mRNA, it sometimes requires a delivery vehicle for its cellular uptake and protects it from degradation by RNases. [ 134 ] mRNA therapeutics have had numerous applications. The use of mRNA vaccines is not limited to infectious diseases.…”
Section: Mrna Therapeuticsmentioning
confidence: 99%
“…In a recent study in 2023, lipid NP functionalized with herpes simplex virus type 1 glycoprotein D and the self-amplifying mRNA induced memory T cell responses that prevented the relapse of subcutaneous tumors and provided strong tumor protection in mouse model [ 72 ]. Interestingly, lipid microparticles with larger size (1150 ± 100 nm) were found to elicit similar effects in cancer prevention when compared to nanoparticle (90.15 ± 2.92 nm and 300 ± 40 nm) [ 200 ].
Fig.
…”
Section: Introductionmentioning
confidence: 99%